Describing the perceptions of bioethics training requirements among young medical professionals: an observational studies - Sucharitha, Sree T.; E., Suganya; Arumugam, Balaji; R. C., Karthik; A., Radhakrishnan; V., Dhanuraja (International Journal Of Community Medicine And Public Health, 2020)
Background: Medical Council of India emphasises the training on bioethics for medical graduates and included the same in medical curriculum reforms. However, the universal implementation of structured training in bioethics remains elusive due to many challenges. Hence the study was planned to describe the perception about the bioethics training needs among trainee interns and junior residents training at tertiary medical teaching hospitals across Tamil Nadu. Methods: A web-based cross-sectional survey was conducted during September-December 2019.Google forms survey was designed, and link was disseminated using affinity groups and snowballing techniques through social media among current medical interns and junior resident doctors working at tertiary care teaching hospital settings across Tamil Nadu. Data was analyzed using MS Excel auto generated through google forms and descriptive statistics were performed. Results: Among 136 respondents of online survey from across 25 medical colleges in Tamil Nadu, 73 (57.5%) were females, 57 (42.2%) had training on bioethics and 31 (54.4%) during internship period. During these trainings, experts in bioethics scholarship conducted training for only 34% of participants. Self-reported inadequate levels of awareness on bioethics was seen in 20.6% subjects and 17.8% subjects professed awareness on Indian Council of Medical Research clinical research ethics guidelines. Combination of curriculum and self-directed learning was the favoured teaching-learning method. Conclusions: This study reveals major gaps in knowledge and attitudes of young medical professionals towards bioethics training and can be addressed through testing novel methods of training.